Mental conditioning effects on glucoside activity in saliva in junior athletes physicality tests - Tambovtseva, R. V.; Nikulina, I. A. (Theory and Practice of Physical Culture, 2019)
Objective of the study was to test effects of a positive mental conditioning on the glucoside activity in the saliva in the beginner junior athletes in standard trainings versus mentally conditioned trainings. Sampled for the study were the 16-17 year-old middle-distance runners (n=21) tested with ergometric and biochemical tests, with the test data processed by a standard mathematical statistics toolkit. The subjects run Monark cycle ergometer at 70% submaximal workload in the standard trainings versus mentally conditioned trainings, with the workload and endurance tests, and with the V.A. Tkachuk glucoside activity in the saliva tests at rest, in the training cycle and 5min after the training. The tests found the positive mental conditioning being of stimulating effect on the glucoside activity in the saliva at every stage of the cycle ergometer test (including the balanced stage, concealed fatigue stage, high fatigue stage and rehabilitation stage), with saliva secretion reduced and saliva density increased on the one hand; and the protein ferments synthesis activation on the other hand, with the ferments disintegrating polysaccharides to produce energy for work.